Neonatal Presentation of an Air-Filled Neck Mass that Enlarges with Valsalva: A Case Report - Jasminkumar Bharatbhai Patel; Howard Kilbride; Lorien Paulson (Thieme Medical Publishers, Inc., 2015)
Abstract Branchial cleft cysts are common causes of congenital neck masses in the pediatric population. However, neonatal presentation of branchial cleft cysts is uncommon, but recognizable secondary to acute respiratory distress from airway compression or complications secondary to infection. We report a 1-day-old infant presenting with an air-filled neck mass that enlarged with Valsalva and was not associated with respiratory distress. The infant was found to have a third branchial cleft cyst with an internal opening into the pyriform sinus. The cyst was conservatively managed with endoscopic surgical decompression and cauterization of the tract and opening. We review the embryology of branchial cleft cysts and current management.